2021
DOI: 10.3390/su13073882
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioural Engagement among Spanish Students in Vocational Education and Training

Abstract: The purpose of this study is to analyse the importance of student engagement in Vocational Education and Training (VET) in Spain. In accordance with this concept, we analyse how emotional engagement (relations with teachers, relations with peers, family support for learning, and perception of family commitment) influences the behavioural engagement (school effort and commitment, school indiscipline) in academic activities of students in basic and intermediate VET. The sample comprises 1180 students (65.4% male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Specifically, this research focuses on the analysis of emotional and behavioural engagement in learning and its connection with the sustainable school environment. Emotional engagement is potentially a mediator of behavioural engagement [18]; therefore, it seemed to us important to explore these dimensions of engagement. Obviously, it makes sense to explore the third dimension-cognitive engagement-as well, so we would see this as a further direction of research.…”
Section: Limitations Future Directions and Practical Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, this research focuses on the analysis of emotional and behavioural engagement in learning and its connection with the sustainable school environment. Emotional engagement is potentially a mediator of behavioural engagement [18]; therefore, it seemed to us important to explore these dimensions of engagement. Obviously, it makes sense to explore the third dimension-cognitive engagement-as well, so we would see this as a further direction of research.…”
Section: Limitations Future Directions and Practical Implementationmentioning
confidence: 99%
“…However, so far, there is a lack of knowledge in the scientific literature on how the sustainable school environment affects students' engagement in learning. Scientific studies show that students' engagement in learning differs based on their individual differences, such as gender [13][14][15][16][17][18], their SES [19], and level of studies [18]. Hence, the focus of this article is to empirically test the different predictions of the sustainable school environment (student cohesiveness, teacher support, peer cooperation, equity, student's perceived autonomy support) for secondary school students' engagement (emotional and behavioural) in learning.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a 2019 study by Durrani et al among Pakistani school principals found a positive correlation between emotional intelligence and transformational leadership. Similarly, a study by Garcia et al (2021) discovered that among a sample of Spanish university professors, emotional intelligence was positively correlated with transformational leadership.…”
Section: Correlation Analysismentioning
confidence: 91%
“…The fact that emotional intelligence abilities like self-awareness, empathy and social skills are necessary for successful leadership can be used to explain the relationship between emotional intelligence and transformative leadership (Garcia et al, 2021). Leaders can inspire and motivate others, foster positive change, and create a positive and engaging work environment by understanding their own emotions as well as those of others.…”
Section: Correlation Analysismentioning
confidence: 99%
“…However, despite the progress made, there are still challenges presented by the development of HVE in China. One of the major challenges is regional inequality, which manifests in the uneven distribution of educational resources, variations in student satisfaction with the learning process, and differences in teacher-student interactions across regions [10][11][12][13]. These disparities have resulted in a shortage of skilled workers in some regions, despite the country's large number of HVE colleges and graduates.…”
Section: Introductionmentioning
confidence: 99%